A CASE Study on Software Project Development Cost, Schedule & Effort Estimation - BVANSS, PRABHAKAR RAO; P, SEETHA RAMAIAH (Asian Journal of Pharmaceutical and Clinical Research, 2017)
This paper theme is to provide a case study of Software Project Development cost, effort, and schedule estimation. From recent past, a remarkableÂ research takes place in developing different techniques on software effort and cost estimation. Making estimation before start of any project isÂ necessary to be able to plan and manage any project. The estimate is an intelligent guess for the project resources. Nowadays, software has becomeÂ a major contributor to economic growth for any nation. Making an estimate before starting any software project is vital for the project managersÂ and key stakeholders. Major project milestones such as project schedules, budgeting, resource allocation, and project delivery dates are set on the effort and cost estimates. Thus, the reliability of the estimation leads any project success or otherwise fail. In this article, author’s idea is to work withÂ function point analysis and include the concept of workforce scheduling in a better way while taking the decision in the contract phase. That leadsÂ to strengthening the relations between the developer and the customer. Basically, size is a main measured unit of the software project. Based on theÂ size and other functionalities, the software managers estimate the total effort required to develop the project. From the effort and work schedule, theÂ total cost can be estimated. Â